Design in the context of posthumanism - Frolova, Natallya U. (Human in the Socio-Cultural Dimension, 2022)
The article is devoted to the questions of position and development of design in the modern situation of transformation changes. Since the end of the last century, human-centred and user-centred paradigms have dominated the scientific discussion on design issues. It can be assumed that today the issues of the consequences of human activities, technological and environmental transformations force designers to focus on social issues. This article examines the existence of design in the era of posthumanism from the perspective of a number of disciplines and perspectives, as well as examples of nascent design practices based on the relationship between human and artificial subjects. Considered this problem of artificial intelligence in the context of transformations in design-practice. Also, this article presents critiques of posthumanism from decolonial theory to consider how emergent design perspectives might better support values such as equality and justice for humans and nonhumans that have been traditionally ignored in design processes. The turn to humanism acquires a new relevance in the context of today’s crisis, promoting not only external but also internal creative development of man, whose resources are inexhaustible. And in this context, design can be the new strategy for the turn toward humanity.
Keywords: design; posthuman design; human-oriented design; posthumanism; artificial intelligence; design of artificial systems; humanism; decolonisation of design